2016
DOI: 10.1183/13993003.00246-2016
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance modifies the association between obesity and current asthma in adults

Abstract: Insulin resistance potentiates the association between obesity and childhood asthma, but this relationship appears inconsistent in relatively small studies of adults. We investigated effect modification in adults using the National Health and Nutrition Examination Survey 2003–2012, a large, nationally representative database. Insulin resistance and a history of physician-diagnosed current asthma were obtained from 12 421 adults, ages 18–85 years. We used logistic regression to determine associations between ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
78
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 35 publications
3
78
0
1
Order By: Relevance
“…Cardet et al analyzed data from 12,421 adult subjects who participated in NHANES. The authors observed a strong association between obesity and current asthma, as expected, but this relationship was stronger in patients in the highest than the lowest tertile of insulin resistance (68). Insulin resistance also amplifies reductions in lung function in overweight or obese adolescents (69, 70).…”
Section: Obesity Increases the Severity Of Asthmasupporting
confidence: 60%
“…Cardet et al analyzed data from 12,421 adult subjects who participated in NHANES. The authors observed a strong association between obesity and current asthma, as expected, but this relationship was stronger in patients in the highest than the lowest tertile of insulin resistance (68). Insulin resistance also amplifies reductions in lung function in overweight or obese adolescents (69, 70).…”
Section: Obesity Increases the Severity Of Asthmasupporting
confidence: 60%
“…Obesity is a component of the metabolic syndrome, a cluster of biochemical and physiological parameters that predispose to cardiovascular disease and systemic inflammation . This has led to interest in whether other components of the metabolic syndrome, such as type 2 diabetes, may be independently associated with asthma development …”
Section: Introductionmentioning
confidence: 99%
“…[9] in this issue of the European Respiratory Journal . These authors investigated associations between obesity and asthma with a focus on effect modification by insulin resistance.…”
mentioning
confidence: 99%
“…This finding by Cardet et al . [9] is topical because recent studies in cell culture and mouse models suggest that insulin can cause lung tissue remodelling and worsen lung function [10]. Specifically, it has been shown that insulin stimulates primary human airway smooth muscle cells to proliferate and release collagen [10].…”
mentioning
confidence: 99%
See 1 more Smart Citation